Over-extremal brane shells from string theory?. (1st December 2022) - Danielsson, Ulf; Van Hemelryck, Vincent; Van Riet, Thomas
Abstract: We demonstrate that, if the usual phenomenological compactifications of IIB string theory with warped throats and anti-branes make sense, there must exist spherical brane shells in 4d that are overcharged. They correspond to classical over-extremal objects but without the usual naked singularities. The objects are made from D3-particles that puff into spherical five-branes that stabilise at finite radii in 4d and whose inside corresponds to the supersymmetric AdS vacuum. One can think of these shells as stabilised Brown–Teitelboim bubbles. We find that these objects can be significantly larger than the string scale depending on the details of the warped compactification.